Identification of MspI Polymorphism in the Forth Intron of Chicken Growth Hormone Gene and Their Associations with Growth Traits in Indonesia Native Chickens - Mu’in, MA; Lumatauw, S (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2013)
Abstract. The objective of this research was to identify MspI polymorphism in the forth intron of chicken growth hormone (cGH) gene and their associations with growth traits in native Indonesian chickens. A total of 72 Indonesia native chickens were genotyped for a locus in the forth intron of cGH gene (cGH-I4/MspI locus) by PCR-RFLP with MspI restriction enzyme. The result showed two genotypes in this locus: AA and BB, with the frequency of 90.28% and 9.72%, respectively. Based on body weight average, B allele had a beneficial effect in increasing the live body weight. The result of General Linier Models analysis indicated that the polymorphism of this locus had significant association (P<0.05) with body weight at 4 months of age and so did the daily gain between 2 to 4 months of age. Therefore, these results suggest that there is a possibility of cGH-I4/MspI locus acting as a genetic marker for growth traits of native Indonesian chickens, especially for body weight at 4 months and daily gain between 2 to 4 months of age.Â Keywords: polymorphism, cGH gene, growth traits, Indonesia native chickens.Â Abstrak.Â Tujuan dari penelitian ini adalah untuk mengidentifikasi polimorfisme MspI intron ke-4 pada gen hormon pertumbuhan ayam (cGH) dan hubungannya dengan sifat pertumbuhan pada ayam asli Indonesia. Sebanyak 72 ekor ayam asli Indonesia diidentifikasi gentotipenya untuk lokus pada intron ke-4 dari gen cGH (cGH-I4/MspI lokus) dengan PCR-RFLP mengguakan enzim restriksi MspI. Hasil penelitian menunjukkan adanya dua genotipe pada lokus ini: AA dan BB , dengan frekuensi masing-masing 90.28 % dan 9,72 %. Berdasarkan rata-rata bobot badan, alel B memiliki pengaruh yang menguntungkan dalam meningkatkan bobot badan hidup. Hasil analisis General Linier Model menunjukkan bahwa polimorfisme lokus ini memiliki hubungan yang nyata (P<0,05 ) dengan bobot badan pada umur 4 bulan dan begitu pula dengan pertambahan bobot badan harian antara umur 2 sampai 4 bulan. Oleh karena itu, hasil ini menunjukkan bahwa ada kemungkinan cGH-I4/MspI lokus bertindak sebagai penanda genetik untuk sifat pertumbuhan ayam asli Indonesia, terutama untuk bobot badan pada umur 4 bulan dan pertambahan bobot badan harian ayam antara umur 2 sampai 4 bulan.Â Kata kunci: polimorfisme , gen cGH , sifat pertumbuhan , ayam asli Indonesia.MA Muâin and S Lumatauw/Animal Production 15(1):1-7, January 2013